Implications of biological activated carbon filters for micropollutant removal in wastewater treatment. (1st February 2021) - Fundneider, T.; Acevedo Alonso, V.; Wick, A.; Albrecht, D.; Lackner, S.
Highlights: Backwashing frequencies are directly linked to biological activity in GAC-filters. 25 micropollutants including transformation products were studied in 6 GAC-filters. Removal of biodegradable micropollutants was observed early on 40 – 50 d. Biological removal in GAC-filters extended the life span by approximately 25 – 42%. GAC-filters have a lower or comparable CUR to PAC applications. Abstract: Granulated Activated Carbon (GAC) filtration is a common process for advanced wastewater treatment. In such filters, the removal of organic substances results from adsorptive as well as biological processes. This work investigated the potential of biological processes and their influence on GAC-filter performance. During 32 months, the removal of micropollutants, Dissolved Organic Carbon (DOC) and the spectral absorption coefficient was monitored in six GAC-filters. The effects of pre-treatment (cloth- and/or membrane-filtration), EBCT (from 6 – 35 min) and GAC-type were evaluated. Likewise, the impact of the influent´s fluctuations in temperature, flow and concentration (ammonia, nitrate, and soluble reactive phosphorus (sRP)) were analysed. Biological processes were tracked by the frequency of backwashing, oxygen consumption, removal of poorly absorbable micropollutants and production of transformation products. Pre-treatment influenced biofilm growth significantly. Membrane filtration delayed the first backwashing event by 122 d in comparison to cloth-filtration, where the first backwash was conducted after only 21 d. Removal of poorly absorbable substances was observed early on (40 – 50 d). Parallel operation contributed to a better utilisation of the GAC-capacity and the biological removal potential. Influent nitrogen species > 0.5 mg N/L promoted biofilm growth, whereas sRP seemed to have no effect. The developed biofilm and optimal operating conditions led to longer life spans of the GAC-filters, making carbon usage rates comparable to those from PAC applications. The results suggest that biological processes accounted for about 25 – 42% of the totally removed DOC at the end of the operation. Graphical abstract: Image, graphical abstract